Herbal extracts: the future treatment option for drug-resistant epilepsy - Mehr Musani,; Muhammad Wasim,; Hassan Salman Siddiqi,; Saara Muddasir,; Fazal Manzoor Arain, (Journal of the Pakistan Medical Association, 2023)
Epilepsy is a neurological disorder characterised by two or more unprovoked seizures. The high prevalence and incidence of epilepsy globally, especially in Asia, has remained a big concern over the course of centuries. Patients are usually prescribed the already known anti-epileptic drugs, but even after going through three different generations of anti-epileptic drugs, some people still suffer from drug-resistant form of epilepsy. These patients are usually prescribed a higher dose of anti-epileptic drugs, which results in more adverse effects. That is why new treatment options, like herbal extracts, should be explored for patients who do not respond to the classic anti-epileptic drugs. The current narrative review was planned to explore if herbal extracts can be the future for the treatment of drug-resistant epilepsy. Key Words: Epilepsy, Herbal extracts, Drug-resistant epilepsy, Anti-epileptic drugs.